Neovascular Glaucoma: Etiology and Staging - Totli Kuruba Mayuri (New Frontiers in Medicine and Medical Research Vol. 16, 2021)
Purpose: To identify the most common cause and the most common stage of presentation of the patient in neovascular glaucoma. Methods: The current study is an observational prospective study. The study comprised 136 eyes from 109 patients with neovascular glaucoma in one or both eyes. Visual acuity, slit lamp biomicroscopy, intraocular pressure (IOP) measurement by Goldmann applanation tonometry, gonioscopy with Posner 4 mirror indirect gonioscope, and dilated fundus examination were all performed on all patients. Neovascularization of iris (NVI) was identified as tuft of new vessels on iris mostly at the pupillary margin in an undilated state, presence of any ectropion uveae, hyphema, anterior chamber reaction, pseudoexfoliative material, keratic precipitates and other signs of uveitis were noted. The number of neovascularized quadrants in the angle was counted. Results: The average age was58.18±13 years, with 80.73 percent of men and 19.26 percent of women. The average IOP was 27.14 ± 11.3 mm Hg. The rubeosis iridis stage was represented by 74 (54.4%), the angle closure stage by 38 (27.9%), and the open angle stage by 24 (17.6%). 89 (65.4%) of the participants had diabetic retinopathy of varying severity, whereas 16 (11.7%) had uveitis and 14 (10.2%) had retinal vein occlusion. The average IOP angle closure stage was 36.53±16.259 mm Hg, much greater than the other two stages (P = 0.000). Conclusion: The most common cause of NVG is proliferative diabetic retinopathy, and rubeosis iridis is the most common stage of presentation, according to the findings of this study.